Analisis Penerapan Total Quality Manajemen dalam Meningkatkan Kinerja Perusahaan - Jukhairia Ritonga; Uci Roito Anggina Nst; Fajar Akbar Nuari (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to find out how the application of TQM affects managerial performance in companies in facing the Globalization Era, especially in the economic field. The method applied in this study is descriptive qualitative by collecting data from previous studies regarding Total Quality Management on employee performance. Based on the research conducted, the results show that TQM, namely customer focus, influences managerial performance with regard to quality, quantity, timeliness, cost effectiveness, and self-reliance as well as how employees perform in optimizing their energy and mind to achieve company goals.